Gout and hyperuricaemia: modifiable cardiovascular risk factors? - Burnier, Michel (Frontiers in Cardiovascular Medicine, 2023)
Gout and hyperuricaemia are two clinical situations associated with an elevated risk of developing cardiovascular (heart failure, myocardial infarction, stroke) and metabolic and renal complications. One reason is probably related to the fact that the prevalence of hyperuricaemia and gout is high in clinical situations, which themselves involve a high cardiovascular risk, such as hypertension, diabetes, chronic kidney disease or obesity. However, recent studies suggest that hyperuricaemia may promote cardiovascular complications independently of other cardiovascular risk factors, by inducing chronic inflammation, oxidative stress, and endothelial dysfunction. The questions that arise today concern primarily the treatment of asymptomatic hyperuricaemia. Should it be treated to decrease the patients’ cardiovascular risk and if so, starting from which level and towards which target? There are now several pieces of evidence indicating that this might be useful, but data from large studies are not unanimous. This review will discuss this issue as well as new well-tolerated treatments, such as febuxostat or SGLT2 inhibitors, which lower uric acid levels, prevent gout and lower the risk of cardio-renal events.